Perbedaan Informasi Citra Diagnostik T2WI Spir dan T2WI Dixon MRI Lumbal Potongan Sagital Dengan Kasus Hernia Nucleus Pulposus (HNP) - Adi Widya Hartana; Kadek Yuda Astina; Triningsih Triningsih (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Herniated nucleus pulposus (HNP) is the leading cause of back pain in old age, occurring as a result of tearing of the fibrous annulus and the nucleus pulposus exiting through the tear. To optimize pathology, fat suppression techniques are needed to suppress fat and fluid. Fat Suppression techniques include Dixon and SPAIR. The use of Dixon is relatively longer but can produce four images at once, while SPIR has the advantage of being more resistant to inhomogeneous magnetic fields. The purpose of this study was to determine the difference between T2WI SPIR and T2WI diagnostic image information Dixon Sagital Cut Lumbar MRI with Hernia Nucleus Pulposus (HNP) cases as well as find out which one is better between the two techniques. The type of research used is quantitative research with an experimental approach that uses prospective data aimed at determining the difference in diagnostic image information T2WI SPIR and T2WI Dixon MRI examination of Sagital Cuts. The study population is patients who perform Lumbar MRI examinations with HNP cases at the Radiology Installation of NTB Provincial Hospital for the period May-July 2023. This study applied total sampling, using a research sample of 17 patients. The results showed a difference in image information between the T2WI SPIR and T2WI Dixon sequences on Lumbar MRI examination of Sagital Cut with a p-velue value smaller than α (<0.05), namely in the anatomy of the Spinal Cord with a p-value (0.021), and the anatomy of the Corpus Vertebraewith value p-value (0.001). The T2 Spir sequence is more optimal in showing anatomical information on the Sagittal Cut lumbar MRI examination compared to the T2 Dixon sequence. due to the more homogeneous emphasis of fat on the anatomy of the Spinal Cord and Corpus Vertebrae